Rasch Model Application to examine the Psychometric Properties of Premarital Sexual Behaviour Scalogram - Ranni Merli Safitri (Journal of Psychology and Instruction, 2020)
The facts of pre-marital sexual behaviour (PSB) in adolescent are worrying, then if this condition continued so Indonesia would have low quality generation both physically and psychologically. This research addressed to validate pre-marital sexual behaviour scalogram. Validation process is essential because the useful measurement tool will be able to reveal pre-marital sexual behaviour in order to acquire a precise and accurate description of adolescents pre-marital sexual behaviour. Four hundred junior high school students participated in this study. Rasch analysis was applied to validate the scalogram that consisted of 10 items ranging from the most until the least PSB committed by participants, using the R program latent trait modelpackage. The results showed that this scalogram is sensitive to describe PSB in both low level (θ < 0) and high level (θ >2,5).